Deskripsi Motivasi Belajar Siswa dan Implikasinya Terhadap Usulan Topik-topik Bimbingan - Paulina Ngobut; Wanti Jocinta Maria Lenny (Jurnal Bimbingan dan Konseling Terapan, 2017)
This study aims to obtain a description of students' learning motivation. Quantitative descriptive research type. Number of research subjects 205 students with side random. The results show that there are no students who have the motivation to learn at very high qualifications and very low. 9 students (5,62%) whose learning motivation is highly qualified, 101 students (63,12) whose learning motivation is high enough and 50 residuals (31,25) whose learning motivation is low qualified. Therefore, it is suggested that guidance topics that can improve students' learning motivation include: learning motivation, learning activities, responsibility, motivation berperstasi, self-concept, self-confidence, processing time, how to organize daily activities, problem solving and learning effective.